Debriefing Tool for Immersive Analytics in Medical Training Simulations - Guths, Leonardo S.; Negrão, Matheus D.; Freitas, Carla M. D. S.; Maciel, Anderson; Torchelsen, Rafael; Nedel, Luciana (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
Immersive technologies enhance training and performance evaluation in fields like medical education. By enabling detailed skill assessment through immersive analytics, Virtual reality (VR) systems also allow instructors to capture and study user interactions in simulated environments, linking theoretical metrics to real-world skill evaluations via behavioral visualization. This paper proposes a system for collecting, storing, and reconstructing user interaction data in medical VR simulations, recording hand movements, 6-DoF positioning, and object manipulation. Data is synchronized to a cloud platform, where a reconstruction process generates a real-time 'ghost avatar' replay with spatial fidelity. Instructors and trainees review sessions immersively using interactive controls to analyze procedural steps, clinical decisions, and deviations from protocol, such as incorrect instrument handling, missteps in sequence, or safety violations within the original spatial context. To validate the tool, a user experiment evaluates the impact of 3D reconstructed scenes on perceived learning and self-assessment. Participants perform predefined tasks, e.g., instrument interaction, and qualitatively compare traditional debriefing with immersive replay, reporting on comprehension and perceived improvements. Results demonstrate that spatially grounded replay enhances perceived feedback precision and can improve training effectiveness compared to conventional methods. Cloud storage ensures scalability for asynchronous review, broadening adoption in resource-constrained settings.